2019
DOI: 10.1111/iwj.13242
|View full text |Cite
|
Sign up to set email alerts
|

Pressure ulcer Cat. II‐IV incidence on the CuroCell S.A.M. PRO powered reactive air support surface in a high‐risk population: A multicentre cohort study in 12 Belgian nursing homes

Abstract: The primary objective was to study pressure ulcer (PU) category II-IV (including suspected deep tissue injury and unstageable PUs) cumulative incidence and PU incidence density, in a 30day observation period, associated with the use of the CuroCell S.A.M. PRO powered reactive air support surface in nursing home residents at risk for PU development. Secondary objectives were to study (a) PU category I cumulative incidence and PU incidence density and (b) user (caregivers and residents) experiences and perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A study of 191 at-risk residents in 12 Belgian nursing homes assessed PI incidence (4.7%) and perceptions of comfort with static air support surfaces. The support surface was found to be comfortable for daily use, and the researchers reported that comfort and sleep quality were essential considerations in the selection of a support surface 60 . Given that some surfaces are associated with higher levels of patient satisfaction and self-reported sleep quality, it seems wise to consider the patient’s individual needs and preferences when selecting a mattress/support surface as well as a repositioning routine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 191 at-risk residents in 12 Belgian nursing homes assessed PI incidence (4.7%) and perceptions of comfort with static air support surfaces. The support surface was found to be comfortable for daily use, and the researchers reported that comfort and sleep quality were essential considerations in the selection of a support surface 60 . Given that some surfaces are associated with higher levels of patient satisfaction and self-reported sleep quality, it seems wise to consider the patient’s individual needs and preferences when selecting a mattress/support surface as well as a repositioning routine.…”
Section: Resultsmentioning
confidence: 99%
“…The support surface was found to be comfortable for daily use, and the researchers reported that comfort and sleep quality were essential considerations in the selection of a support surface. 60 Given that some surfaces are associated with higher levels of patient satisfaction and self-reported sleep quality, it seems wise to consider the patient's individual needs and preferences when selecting a mattress/ support surface as well as a repositioning routine. If preferences cannot be determined because of cognitive disability, consider how the surface is affecting the patient, which surface is appropriate, and the patient's individualized turning schedule.…”
Section: Sleep Support Surface Sleep Deprivation and Repositioningmentioning
confidence: 99%
“…Hopkins et al 17 described equipment‐related pain and comfort 17 . Other studies have reported on “patient comfort” and “quality of sleep” 32,33,35 . The following themes were described by Nixon et al 12 : “mattress noise,” “interference with sleep,” “affected by mattress motion,” “movement in bed,” “movement getting in and out of bed,” and “overall comfort.”…”
Section: Discussionmentioning
confidence: 99%
“…Three of these reasons (noise, uncomfortable beds, and pain) can be related to the use of the mattress. Patient comfort and sleep quality are essential criteria in the selection of a support surface 35 . Healthcare professionals should be aware that the implementation of a new type of support surface has an impact on nursing home residents.…”
Section: Discussionmentioning
confidence: 99%